Advances in our understanding of the pathology of chronic intestinal pseudo-obstruction. Issue 11 (11th October 2004) - De Giorgio, R; Sarnelli, G; Corinaldesi, R; Stanghellini, V
Abstract : Chronic intestinal pseudo-obstruction (CIP) represents a particularly difficult clinical challenge. It is a rare and highly morbid syndrome characterised by impaired gastrointestinal propulsion together with symptoms and signs of bowel obstruction in the absence of any lesions occluding the gut lumen. CIP can be classified as either "secondary" to a wide array of recognised pathological conditions or "idiopathic" (CIIP). This review will focus on CIIP, and specifically on the underlying pathological abnormalities. Combined clinical and histopathological studies are needed to highlight new perspectives in the understanding and management of chronic intestinal pseudo-obstruction.